The Impact of Tourism on the Economy in the Destination of Ubud After the Lifting of Travel Restrictions - Pratama, I Gusti Ngurah Wibawa; Lilasari, Luh Nyoman Tri; Widana, Ida Bgs Gede Agung (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This study aims to assess the impact of tourism on the economy in Ubud after travel restrictions were lifted, focusing on people working in the tourism sector. The study involved 150 respondents selected through purposive sampling and accidental sampling. Data analysis was conducted using descriptive statistics and confirmatory factor analysis. The results show that the impact of tourism in the Ubud destination after the lifting of travel restrictions which has the highest average value in each variable begins with an increase in souvenir sales with an average of 4.53, increasing market prices for local handicraft products with an average of 4.44, and increasing employment opportunities for local workers with an average of 4.60. The most felt economic impact in the direct impact section is an increase in the availability of local crafts with a CFA value of 0.751, then in the indirect impact there is the most felt impact of increased government spending on promotion with a CFA value of 0.898, and in the induced impact is an increase in the use of local labor with a CFA value of 0.875.